The Self-Governance Shift: Reposisi Etika Profesi Akuntansi dalam Ekosistem Work from Anywhere - Sanditha, Fidia; Zahra, Nabilah Amalia; Aurelia, Dini; Yusnaini, Yusnaini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The transition toward a Work From Anywhere (WFA) ecosystem has triggered a fundamental "Self-Governance Shift," challenging the traditional social contract of the accounting profession. This study investigates the repositioning of professional ethics as physical boundaries dissolve, threatening conventional surveillance mechanisms. Employing a Systematic Literature Review (SLR) of 25 high-impact studies from 2022–2025, the research synthesizes how professional integrity is being reconstructed in decentralized digital spaces. The findings debunk the assumption that the absence of physical oversight inherently compromises audit quality. Instead, a new paradigm of "autonomous professionalism" emerges, in which ethical conduct is moderated by auditor self-efficacy, digital fluency, and results-oriented accountability rather than by institutional presence. A critical discovery is that client technological readiness is a vital moderator that mitigates agency risks and information asymmetry in remote audits. By integrating Agency, Social Determination, and Accountability theories, this study proposes a structural evolution from external institutional control to internal moral maturity. These insights offer a strategic roadmap for regulators to redesign ethical frameworks for the algorithmic age. Ultimately, the "Self-Governance Shift" redefines the auditor as a self-regulating moral agent, ensuring public trust remains resilient despite the radical decentralization of the professional workspace. This shift marks a permanent evolution in the global accounting landscape, demanding higher standards of individual ethical internalization in the digital era.